Strategy for Handling Musculoskeletal Problems in Employees of Kediri District Hospital - Riska Jeje Nur’aini; Fahma Yulinda Ekasari; Maritha Devi; Verin Firstania; Novita Ana Anggraini5 (Universitas STRADA Indonesia, 2025)
Office employees who work with computers typically spend prolonged periods—approximately 8 hours per day from morning until evening, five consecutive days a week (Monday to Friday) characterized by static working postures and limited physical activity. Musculoskeletal problems such as complaints of neck, shoulder, back and knee pain are often found by RSUD Kabupaten Kediri employees. This condition can cause musculoskeletal disorders, which can significantly reduce work productivity. Therefore, a residency is conducted to develop community-based physiotherapy services. An analysis was conducted, followed by the implementation of solutions through awareness campaigns, educational sessions, and the distribution of brochures discussing ergonomic posture, musculoskeletal pain, and prevention and management strategies. The study was carried out for one month and involved 10 respondents who met the inclusion criteria using purposive sampling. Research instruments included the Nordic Body Map, VAS, and RULA. The Fishbone diagram, USG method, and SWOT analysis was used in this recidency.Education and socialisation have been proven effective in reducing musculoskeletal complaints among employees who work with computers at RSUD Kabupaten Kediri. Additionally, prevention and management strategies, such as self-guided stretching exercises, can alleviate musculoskeletal pain, while awareness campaigns about proper ergonomic practices when using computers are also crucial for preventing musculoskeletal issues.